Association between Serum Interleukin-17A Level and High-Altitude Deacclimatization Syndrome. (14th April 2016) - He, Binfeng; Li, Hongli; Hu, Mingdong; Dong, Weijie; Wei, Zhenghua; Li, Jin; Yao, Wei; Guo, Xiaolan
Abstract : High-altitude deacclimatization syndrome (HADAS) is emerging as a severe public health issue that threatens the quality of life of individuals who return to lower altitude from high altitude. In this study, we measured serum levels of SOD, MDA, IL-17A, IL-10, TNF- α, and HADAS score in HADAS subjects at baseline and 50th and 100th days and to evaluate the relationship between interleukins, including IL-17A, and HADAS. Our data showed that and the serum IL-17A levels and HADAS score decreased over time in the HADAS group, and serum IL-17A levels were significantly higher in the HADAS group at baseline and 50th day compared with controls (p < 0.05 ). Furthermore, baseline serum levels of MDA and TNF- α were significantly higher, while SOD and IL-10 levels were lower in HADAS subjects compared with controls (p < 0.05 ). It is interesting that serum levels of IL-17A were clearly interrelated with HADAS incidence and severity (p < 0.05 ). ROC curve analysis showed that combined serum IL-17A and IL-10 levels were a better predictor of HADAS incidence than serum levels of IL-17A or IL-10 alone. These data suggest that serum levels of IL-17A are a novel predictive index of HADAS.